Book review: Prem Chowdhry, Gender, Power and Identity: Essays on Masculinities in Rural North India. (October 2020) - Bhardwaj, Shivani
Prem Chowdhry, Gender, Power and Identity: Essays on Masculinities in Rural North India . Hyderabad: Orient BlackSwan, 2019, 288 pages, ₹795 (Hardcover). ISBN: 978-93-5287-657-0.